Persepsi dan Faktor Dominan Determinan Minat Pelaku Usaha Mikro Kecil Muslim Pengguna Jasa Pelepas Uang terhadap Jasa Lembaga Keuangan Mikro Syariah - Penny Rahmah Fadhlilah (Majalah Sainstekes, 2017)
This study aim is to determine the perceptions and interests of Micro and Small Business Enterprises (MSEs) of small micro business users of the Muslim money lenders against Islamic Microfinance institution services. To view and analyze the five factors of interest used in personal, environment, convenience, service, and debt. Based on the five factors mentioned, the dominant factor that formed the interest will be distinguished. This research was conducted in Bogor City Walk with the sample of 57 respondents. Data was collected by questionnaire survey using the tools that have been tested for validity and reliability. Analysis of study factors to see the interest is done by using factor analysis while to view the perception used descriptive statistik. The results of the factor analysis showed interest in the perpetrator obtained the conclusion that Muslim enterprises used money lenders service users against the Islamic financial services are caused by sosial factors : the magnitude of motivation, ease the requirements, and strategic location.